The Role of Government in Efforts to Resolve Labor Conflicts on Industrial Relations in The Company - Efran Dinata; Efendi Sugianto (Yayasan Riset dan Pengembangan Intelektual, 2024)
Your research approach seems thorough and well-structured, focusing on providing a comprehensive understanding of the role of the government in resolving labor relations conflicts in Indonesia. By using a qualitative descriptive approach and collecting data from various sources, including library research and field surveys, you aim to gain insights into the strategies, policies, and mechanisms employed by the government in addressing these conflicts. The qualitative method with an exploratory approach is suitable for delving into the complexity and dynamics of the government's role in resolving labor relations conflicts. This approach allows for a deeper understanding of the nuances and contextual factors involved in such disputes. Your findings regarding the government's active role in resolving labor relations conflicts are supported by data from the Industrial Relations Court. The comparison between cases resolved at the tripartite level and those escalated to the industrial court level provides valuable insights into the effectiveness of government intervention at different stages of conflict resolution. Overall, your research appears to provide valuable insights into the role of the government in labor relations conflicts in Indonesia and lays a solid foundation for further analysis and evaluation of the impact of government strategies and policies on stability in this context.